The corrosion characterization of a ferritic stainless steel with Mo addition in H2SO4 and HCI acid solutions - Demiroren, H.; Aksoy, M.; Yildiz, T.; Buytoz, S. (Maik Nauka/Interperiodica/Springer, 2009)
The corrosion behavior of ferritic stainless steel containing 1 wt, % Mo was investigated using an AC impedance technique and the mass loss method. The alloys were produced by casting and forging. They were classified into three groups: unhomogenized, homogenized for 30 minutes and homogenized for 180 minutes. Mass loss tests were carried out on samples homogenized for 180 minutes. The corrosion tests were performed in 0.1 M H2SO4 and 0.3 M HCl acid solutions. SEM investigations were performed on the surface of samples exposed to corrosion for 30 and 360 minutes. The results were compared with results obtained from experiments performed on unalloyed ferritic stainless steel. Molybdenum (Mo) and homogenization heat treatment were found to have a beneficial effect on corrosion behavior of ferritic stainless steel in these solutions.
Keywords: Alloyed Molybdenum; Dissolution; Passivation; Resistance; Impedance; Behavior; Nickel; Films